TOURIST PERCEPTIONS ON THE ATTRACTION OF KALOMANG BEACH TOURISM OBJECTS IN WATUBANGGA DISTRICT, KOLAKA REGENCY - Irvan Siswanto; Nasarudin Nasarudin; Sudarwin Kamur (USN Kolaka, 2022)
This research aims to describe the characteristics of tourists who visit the Kalomang Beach tourist attraction, as well as the tourists' perceptions of the attractiveness of the Kalomang Beach tourist attraction in terms of the dimensions of tourist attractions, accessibility, facilities, and services. This research is a type of quantitative descriptive research with respondents, namely all tourists who visit the Kalomang Beach tourist attraction. Determination of the sample using the Corchan formula and obtained a sample of 100 respondents with a sampling technique that is incidental sampling. Data collection using interview techniques, questionnaires and documentation; the data processing in this research used a tabular descriptive analysis technique. The results showed that tourists' perceptions of the attractiveness of the Kalomang Beach tourist attraction in terms of the dimensions of attractions, accessibility, amenities, and service overall got a good category from tourists. Judging from the dimensions of attractions, Kalomang Beach got a score of 384.75 with a good category from tourists; for the accessibility dimension, it got a score of 416.5 with an excellent category from tourists. The amenities dimension got a score of 377,375 with a good category from tourists, and finally, the service dimension got a score of 385.5 with a good category from tourists.